2017
DOI: 10.1007/s00702-017-1780-1
|View full text |Cite
|
Sign up to set email alerts
|

Is nigrostriatal dopaminergic deficit necessary for Holmes tremor to develop? The DaTSCAN and IBZM SPECT study

Abstract: Holmes’s tremor (HT) is assumed to be the result of coexistence of nigrostriatal dopaminergic system impairment and the lesion of cerebello-thalamic pathways. It was suggested that dopaminergic deficiency is responsible for rest tremor, and lack of compensatory cerebellar function leads to spill of tremor into voluntary movements. Cases of HT with and without abnormalities of the presynaptic part of dopaminergic nigrostriatal were published and these findings raised the question of possibility of the postsynap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The nigrostriatal tract was also not a key part of our Holmes tremor circuit, despite dopaminergic medication being a first line treatment for Holmes tremor . This result aligns with other data suggesting that nigrostriatal tract involvement is not necessary for development of Holmes tremor . Specifically, many patients with Holmes tremor have normal dopamine neuroimaging and only half of patients respond to dopaminergic medication …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The nigrostriatal tract was also not a key part of our Holmes tremor circuit, despite dopaminergic medication being a first line treatment for Holmes tremor . This result aligns with other data suggesting that nigrostriatal tract involvement is not necessary for development of Holmes tremor . Specifically, many patients with Holmes tremor have normal dopamine neuroimaging and only half of patients respond to dopaminergic medication …”
Section: Discussionsupporting
confidence: 91%
“…4 This result aligns with other data suggesting that nigrostriatal tract involvement is not necessary for development of Holmes tremor. 32 Specifically, many patients with Holmes tremor have normal dopamine neuroimaging and only half of patients respond to dopaminergic medication. 4,5,[32][33][34] Given that all 36 lesion locations causing Holmes tremor were connected to a common circuit, this connectivity could be considered necessary for a lesion to cause Holmes tremor.…”
mentioning
confidence: 99%
“… 6 Current research shows that involvement of the substantia nigra and striatum is not necessary for the occurrence of HT. 7 Specifically, many patients with HT have normal dopamine levels as measured via neuroimaging, and only half of such patients respond to dopaminergic medication. 4 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed tremor amplitude-related activity in the sensorimotor cortex and cerebellar vermis in a patient with Holmes tremor caused by a microbleed near the right red nucleus that caused ipsilateral nigrostriatal dopaminergic denervation [85]. Nigrostriatal dopaminergic denervation is a variable finding in Holmes tremor and does not always correspond to a good levodopa responsiveness [83,[85][86][87]. Therefore, it has been suggested that lesions causing Holmes tremor do not localize to any single region, but instead localize to a functionally connected network [84].…”
Section: Holmes Tremormentioning
confidence: 99%